Answer:
![\left \{ {{y=x^(2) } \atop {y=x^2+2x+9}} \right.](https://img.qammunity.org/2020/formulas/mathematics/high-school/yha54nbquzlfx91bkmlgn8n47cut105x3e.png)
Explanation:
1. As you can see,
is equal to the other quadratic equation
.
2. Then, this would the same as write the quadratic equations as following:
![y=x^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qfh1zkisge7wtl99lc0zrsdplbk57w91cd.png)
![y=x^2+2x+9](https://img.qammunity.org/2020/formulas/mathematics/high-school/5s0vkd97if5ytdlytq3xdjmu5be5ynw9fz.png)
3. And then set them equal to each other, as you can see below:
![y=y](https://img.qammunity.org/2020/formulas/mathematics/high-school/d4ybdrclwj1grtud7lo4sujp8xlqdw3ry5.png)
Substituting, you obtain:
![x^(2)=x^2+2x+9](https://img.qammunity.org/2020/formulas/mathematics/high-school/rfi8ydi1g81rqowzzby2c7tj8t6rwj5t7t.png)
3. Keeping the above on mind, you can set up the given equations as a system of equations as folllowing:
![\left \{ {{y=x^(2) } \atop {y=x^2+2x+9}} \right.](https://img.qammunity.org/2020/formulas/mathematics/high-school/yha54nbquzlfx91bkmlgn8n47cut105x3e.png)